DEVELOPING LISTENING AND SPEAKING SKILLS INTENSIVELY - Shoimova Dilobar,; Sherqobilova Sabrina,; Safarova DIldora, (Ustozlar uchun, 2025)
This article explores the importance of intensive training in listening and speaking skills in language acquisition. It highlights effective strategies, benefits, and modern tools that support learners in achieving fluency and confidence. Emphasis is placed on real-life practice, multimedia tools, and interactive approaches that promote active communication. The article also provides recommended resources for further study, including books and websites.